2007
DOI: 10.1021/jp0727493
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Photocatalytic Activity, and Mechanism of Nano-TiO2 Co-Doped with Nitrogen and Iron (III)

Abstract: Nanoparticles of titanium dioxide co-doped with nitrogen and iron (III) were first prepared using the homogeneous precipitation-hydrothermal method. The structure and properties of the co-doped were studied by XRD, XPS, Raman, FL, and UV-diffuse reflectance spectra. By analyzing the structures and photocatalytic activities of the undoped and nitrogen and/or Fe 3+ -doped TiO 2 under ultraviolet and visible light irradiation, the probable mechanism of co-doped particles was investigated. It is presumed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
267
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 501 publications
(278 citation statements)
references
References 26 publications
10
267
0
1
Order By: Relevance
“…Cong et al 26 reported that the peak in the range of 397-401 eV was the N1s peak when using the wet chemical method, whereas other methods should exhibit the N1s peak around 396 eV. Besides, according to the previous literatures about prepration of N doped TiO 2 using N 2 plasma treatment, 27 the peaks around 396 eV are attributed to substitution of crystallattice oxygen of TiO 2 to form Ti-N bond.…”
Section: Methodsmentioning
confidence: 97%
“…Cong et al 26 reported that the peak in the range of 397-401 eV was the N1s peak when using the wet chemical method, whereas other methods should exhibit the N1s peak around 396 eV. Besides, according to the previous literatures about prepration of N doped TiO 2 using N 2 plasma treatment, 27 the peaks around 396 eV are attributed to substitution of crystallattice oxygen of TiO 2 to form Ti-N bond.…”
Section: Methodsmentioning
confidence: 97%
“…In addition, the different nitrogen source may also influence the characteristics of the nitrogen state. Cong et al 20 reported that the peak in the range of 397-401 eV was the N1s peak when using the wet chemical method. The N1s peaks of NTiO 2 and Mo-N-TiO 2 are all around 399 eV, which are attributed to the N1s electron binding energy of the N atom in the environment of O-Ti-N. 21 These binding energies are higher than the typical binding energy of 396.9 eV in TiN.…”
Section: Resultsmentioning
confidence: 99%
“…Through years of development, the dopants change from metal ions [1][2][3][4][5][6][7] to nonmetal ions [8][9][10], and the doping method develop from single doping to codoping [11][12][13][14]. Carbon is one of the most adopted nonmetal dopants both in single doping and codoping.…”
Section: Introductionmentioning
confidence: 99%